Color Tuning and Optical Temperature Sensing Properties of Upconversion Emission in Yb3+/Er3+/Tm3+Doped Boro-Zinctellurite Glasses - Eryurek, Gonul; Tabanli, Sevcan; Buhari, Thami; Erdem, Murat (The Electrochemical Society, 2023)
Zinc borotellurite (B2O3/BaO/ZnO/TeO2) glasses co-doped with Tm3+/Yb3+, Er3+/Yb3+ and tri-doped Tm3+/Er3+/Yb3+ were prepared using the traditional melt quenching method. Optical absorption spectra were measured in the wavelength range of 350 nm-1100 nm at room temperature. The optical bandgap (Eg) and Urbach energy were calculated from Tauc’s plot. Blue and green emissions that can be seen by the naked eye were generated under 975 nm laser light excitation in doped Tm3+/Yb3+ and Er3+/Yb3+ doped glasses. Shifts in both blue and green color coordinates were seen as the excitation power density increased from 0.5 to 15.1 W cm−2. A white light generation was generated in glass doped with Tm3+/Er3+/Yb3+ ions, although a noticeable shift was not observed in both blue and green color coordinates for the same excitation power density range. Temperature sensing properties were investigated using the fluorescence intensity ratio of upconversion green emissions from the two thermally coupled 2H11/2 and 4S3/2 levels of Er3+ ions between 304 K and 443 K. The maximum sensitivity of the glasses doped with Er3+ and Er3+/Yb3+ were found to be 7.2 × 10−3 K−1 and 1.2 × 10−2 K−1 at 429 K, respectively.